Identifikasi Kemampuab Berpikir Kreatif Siswa Kelas VIII SMP Mambaul Hisan Ngadiluwih Kediri dalam Pemecahan Masalah Materi Tekanan Zat - Siti Afidatul Karomah; Husni Cahyadi Kurniawan; Nani Sunarmi (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
The ability to think creatively is very important for students in the learning process, especially physics. Then a study was conducted that aimed to identify the level of creative thinking ability of Class VIII SMP Mambaul Hisan Ngadiluwih Kediri in solving the problem of substance pressure. Aspects of creative thinking skills tested include fluency, flexibility, originality, and elaboration. Collecting data through written tests and interviews, where the data obtained in the form of quantitative data and then analyzed descriptively. The results showed that the creative thinking skills of high-ability students were at level 3, namely being creative and able to fulfill the three aspects tested. Students of moderate ability are at level 2 which is creative enough to be able to fulfill the two aspects tested. Low ability students are at level 1 and level 0, level 1 students are less creative only meet one aspect and level 0 students have not fulfilled one aspect of creative thinking tested.